Gondwanan Origin of Bark and Ambrosia Beetles and Their Rapid Worldwide Diversification During the Cretaceous - Jules Ferreira; Fabien L. Condamine; Laura Pajot; David Peris; Bjarte H. Jordal (Journal of Biogeography, 2026)
Aim It is not trivial to estimate the relative contributions of dispersal, vicariance, and range contraction in explaining the present‐day distribution of ancient clades. In this study, we aim to infer the historical biogeography of bark and ambrosia beetles using a genus‐level time‐calibrated molecular phylogeny that encompasses 70% of all described genera. We also evaluate the potential influence of external factors, such as host‐plant associations, feeding strategies, and tectonic events, on their spatial patterns over time. Location Worldwide. Taxon Scolytinae (Coleoptera: Curculionidae). Methods We conducted molecular phylogenetic analyses of Scolytinae at the genus level and dated the results tree using node dating and updated timeframe from the most recent work on the age of Scolytinae. Using the ‘BioGeoBEARS’ R package with a time‐stratified framework based on past landmass configurations, we inferred the ancestral ranges of the subfamily and its tribes across its whole evolutionary history. Results Our results support a Gondwanan Cretaceous origin of Scolytinae in the Afrotropical–Neotropical regions ( ca . 134 Ma). Earliest splits occurred between the Afrotropics and Neotropics, largely mirroring the fragmentation of the Gondwanan landmass. More recent dispersal events were directed toward the Oriental, Nearctic, Australasian, Indian Ocean (notably Madagascar), and the Pacific regions. Main Conclusions Early distributions were concentrated in tropical regions such as the Afrotropics and Neotropics, but also part of the Palearctic (Western part), where Early Cretaceous woody angiosperm fossils are documented. More recent and significant expansions occurred into the Nearctic and Oriental regions. Subsequent independent host shifts to gymnosperms in some lineages may have facilitated colonisation of temperate zones, including part of the Palearctic and Nearctic. While range contraction events did occur, they were comparatively few and scattered, compared to range expansions that clearly dominated the evolutionary history of the group, highlighting the strong resilience of Scolytinae through time.

Experimental study about frost formation and growth in the evaporator of an air-to-water heat pump - David Alarcón-Gallén; Javier Marchante-Avellaneda; Abdelrahman H. Hassan; Emilio Navarro-Peris (International Journal of Refrigeration, 2025)

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

Postglacial History of a Widespread Wood‐Decaying Fungus in Europe Suggests Migration out of Multiple Refugia Followed by Admixture - Dabao Sun Lu; Ine‐Susanne Hopland Methlie; Jørn‐Henrik Sønstebø; Anneli Andersen; David Peris; Sundy Maurice; Håvard Kauserud; Inger Skrede (Molecular Ecology, 2025)
While postglacial migration patterns have been well‐studied in plants and animals in Europe, the same is not true for microorganisms such as fungi, and it remains unclear whether fungi have followed the same postglacial migration trajectories. In this study, we infer the postglacial history of the widespread wood‐decay fungus Trichaptum abietinum in Europe. We investigate whether this fungus resided in multiple glacial refugia, as observed in many plants and animals, and how it migrated following the retreat of the ice. Population genomic analyses of T. abietinum suggest at least two glacial refugia in Europe: a southern refugium extending from Portugal to the Caucasus (potentially formed by several earlier distinct refugia), an eastern refugium and a potential third western refugium. Expansion from these refugia followed by migration and secondary contact has led to a complex genomic pattern of what we call the Mediterranean, Boreal, Atlantic and Central European admixed groups. From the southern and potential western refugia there have likely been northwards expansions resulting in the Mediterranean and Atlantic groups, while the Boreal group probably expanded westwards from the eastern refugium. A contact zone is present in Central Europe, where the Mediterranean and Boreal groups are admixing. In these admixed individuals, the second half of their largest scaffold is entirely inherited from the Boreal group, indicating either strong selection or genomic incompatibilities. In Scandinavia, the Atlantic and Boreal groups are in close contact but with limited admixture. Tajima's D and analyses of linkage disequilibrium decay support a recent history of contraction and expansion of this fungus in Europe. We conclude that the postglacial migration patterns in T. abietinum resemble those observed in several plants and animals, suggesting multiple glacial refugia followed by admixture during northward and westward expansions.

Antioxidant-related enzymes and peptides as biomarkers of metallic nanoparticles (eco)toxicity in the aquatic environment - Tomas Do; Silvia Vaculciakova; Katarzyna Kluska; Manuel David Peris-Díaz; Jan Priborsky; Roman Guran; Artur Krężel; Vojtech Adam; Ondrej Zitka (Chemosphere, 2024)

Parametric fire curves for I-girder bridges submitted to under deck tanker fires - Jethro David Howard; Ignacio Paya-Zaforteza; Guillem Peris-Sayol (Engineering Structures, 2024)

Prolonged cold-preservation of domestic cat ovarian tissue is improved by extracellular solution but impaired by the fragmentation of ovary - Olga Rodak; Manuel David Peris-Diaz; Piotr Dzięgiel; Aleksandra Piotrowska; Agnieszka Partyka; Wojciech Niżański (Animal Reproduction Science, 2024)

Insect pollination in deep time - Constanza Peña-Kairath; Xavier Delclòs; Sergio Álvarez-Parra; Enrique Peñalver; Michael S. Engel; Jeff Ollerton; David Peris (Trends in Ecology & Evolution, 2023)

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Phylogeography of the wild Lager‐brewing ancestor ( Saccharomyces eubayanus ) in Patagonia - Juan I. Eizaguirre; David Peris; María E. Rodríguez; Christian A. Lopes; Patricio De Los Ríos; Chris Todd Hittinger; Diego Libkind (Environmental Microbiology, 2018)
Summary Saccharomyces eubayanus is the close relative of the Lager‐brewing yeast and was firstly found in North Patagonia associated with Nothofagus trees. In recent years additional strains were found in North America, Asia and New Zealand, and genomic analyses showed the existence of two main populations of this yeast, both of them present in Patagonia. Here, we performed the most comprehensive study of S. eubayanus in Patagonia natural environments (400 samples) and confirmed that this region has the highest isolation success rate for this species described worldwide (more than 10‐fold). The genetic characterization of 200 isolates ( COX2 , DCR1 , intFR ) revealed five geographically structured subpopulations. We hypothesized that marine ingressions and glaciations, which shaped the Patagonian landscape, contributed on population differentiation. The first large screening of fermentation performance of 60 wild S. eubayanus strains indicated which subpopulations would be more suitable for beer production.

New ambrosia beetles (Coleoptera: Curculionidae: Platypodinae) from Miocene Mexican and Dominican ambers and their paleobiogeographical implications - David Peris; Mónica M. Solórzano Kraemer; Enrique Peñalver; Xavier Delclòs (Organisms Diversity & Evolution, 2015)

Fossil Monotomidae (Coleoptera: Polyphaga) from Laurasian Cretaceous amber - David Peris; Xavier Delclòs (Organisms Diversity & Evolution, 2015)

Population structure and reticulate evolution of S accharomyces eubayanus and its lager‐brewing hybrids - David Peris; Kayla Sylvester; Diego Libkind; Paula Gonçalves; José Paulo Sampaio; William G. Alexander; Chris Todd Hittinger (Molecular Ecology, 2014)
Reticulate evolution can be a major driver of diversification into new niches, especially in disturbed habitats and at the edges of ranges. Industrial fermentation strains of yeast provide a window into these processes, but progress has been hampered by a limited understanding of the natural diversity and distribution of S accharomyces species and populations. For example, lager beer is brewed with S accharomyces pastorianus , an alloploid hybrid of S . cerevisiae and S . eubayanus , a species only recently discovered in P atagonia, A rgentina. Here, we report that genetically diverse strains of S . eubayanus are readily isolated from P atagonia, demonstrating that the species is well established there. Analyses of multilocus sequence data strongly suggest that there are two diverse and highly differentiated P atagonian populations. The low nucleotide diversity found in the S . eubayanus moiety of hybrid E uropean brewing strains suggests that their alleles were drawn from a small subpopulation that is closely related to one of the P atagonian populations. For the first time, we also report the rare isolation of S . eubayanus outside P atagonia, in W isconsin, USA . In contrast to the clear population differentiation in P atagonia, the N orth A merican strains represent a recent and possibly transient admixture of the two P atagonian populations. These complex and varied reticulation events are not adequately captured by conventional phylogenetic methods and required analyses of B ayesian concordance factors and phylogenetic networks to accurately summarize and interpret. These findings show how genetically diverse eukaryotic microbes can produce rare but economically important hybrids with low genetic diversity when they migrate from their natural ecological context.